Efficient perovskite solar cell fabricated in ambient air using one-step spin-coating. Issue 49 (3rd May 2016) - Wang, Gang; Liu, Debei; Xiang, Jin; Zhou, Dachen; Alameh, Kamal; Ding, Baofu; Song, Qunliang
Abstract : The higher film coverage and better device performance is achieved for film spin-coated in air and then annealed in vacuum. Abstract : One-step spin coating is a simple method which has been widely used in fabricating perovskite solar cells. However, this method was vastly demonstrated in glove box wherein the influence of moisture is negligible. Thus the use of one-step spin-coating in ambient air has not been comprehensively investigated. In this work, we employ one-step spin-coating method to coat perovskite films in ambient air (with humidity above 50%), and then the perovskite films are annealed in vacuum or air. Experimental results show that by using vacuum annealing, a power conversion efficiency of 12.98% is attained, and this is 45% higher than that attained by air annealing method. This improvement is mainly attributed to the fast solvent evaporation process in vacuum during annealing, which induces high supersaturation that leads to higher coverage of perovskite film.